Pengaruh Atraksi Wisata dan Harga Terhadap Motivasi Berkunjung Wisatawan di Situ Cangkuang - Rieke Sri Rizki Asti Karini; Zakiah Tuffahati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
This research aims to determine the effect of tourist attractions and prices on visiting motivation. This is based on the decline in the number of tourist visits to Situ Cangkuang from 2019 to 2022. Factors that cause a decrease in the number of visits are attractions and price that has an impact on visiting motivation. The purpose of this study in determine the effect of tourist attractions and prices has an the impact on visiting motivations in Situ Cangkuang. The study was conducted in Situ Cangkuang by taking 100 tourists as respondents. This research uses descriptive and verification methods with a quantitative approach. Data obtained from questionnaires that have been distributed and then processed using SPSS Statistics 25 for Windows software. The results showed that tourist attractions and prices have a positive and significant correlation of 0,706 (70,6%). The through the F test shows that tourist attractions and prices simultaneously influence visiting motivation significantly. The adjusted R squer number of 0,498 (49,8%) of visiting motivation variables can be expalined through two independent variables in the regression equation. While the remaining 50,2% is explained by ither variables excluding the two variables used in this study.